2015
DOI: 10.1002/ghg.1509
|View full text |Cite
|
Sign up to set email alerts
|

Wetted‐wall column study on CO2 absorption kinetics enhancement by additive of nanoparticles

Abstract: Nanoparticles suspended in solutions are considered to have the potential to enhance gas‐liquid mass transfer and have been studied for gas separation. In order to reveal the mechanisms of kinetics enhancement, the diffusion and reaction process should be carefully examined. In this paper, CO2 absorption kinetics of amine‐based solutions with additive of SiO2 and Al2O3 nanoparticles were investigated by wetted‐wall column experiments. Measurements at different conditions, including solid loading, pressure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Model for CO 2 Diffusivity in the Liquid Phase. Because of our previous work, 14 the CO 2 absorption into MEA satisfies the pseudo-first-order reaction conditions. So, k L is the function of the kinetic rate constant (k 2 , expressed in terms of m 3 /(mol s)), the bulk concentration of solvent in the liquid phase (C sol bulk , given in units of mol/m 3 ), the CO 2 diffusion coefficient in the liquid phase (D CO 2 L , given in units of m 2 /s), and the Henry's law constant for CO 2 in the liquid phase (H CO 2 , expressed in terms of Pa m 3 /mol):…”
Section: Theoretical Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model for CO 2 Diffusivity in the Liquid Phase. Because of our previous work, 14 the CO 2 absorption into MEA satisfies the pseudo-first-order reaction conditions. So, k L is the function of the kinetic rate constant (k 2 , expressed in terms of m 3 /(mol s)), the bulk concentration of solvent in the liquid phase (C sol bulk , given in units of mol/m 3 ), the CO 2 diffusion coefficient in the liquid phase (D CO 2 L , given in units of m 2 /s), and the Henry's law constant for CO 2 in the liquid phase (H CO 2 , expressed in terms of Pa m 3 /mol):…”
Section: Theoretical Fundamentalsmentioning
confidence: 99%
“…Wang et al established masstransfer models in nanofluids to estimate the increased CO 2 diffusivity into MEA in a wetted-wall column and found that the microconvective motion contributed ∼80% of the increased CO 2 diffusivity in liquid bulk, which supports the reliability of the shuttle effect and the boundary mixing effect. 14 Kim used high-speed camera images of CO 2 bubbles in methanol/Al 2 O 3 mixture, but did not observe bubbles breaking in nanofluids. 13 For better understanding of nanoparticles roles in mass-transfer enhancement, it is necessary to establish the methodology that can be used to quantify these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is also not suitable for industrial application since a higher viscous solvent leads to a longer residence time and larger equipment size [50]. Utilizing nanoparticles into solvents can significantly increase the viscosity of the solvent [51]. This limits gas diffusion and pumping, which impacts the total cost and energy of the process [52].…”
Section: Fluid Mechanics and Flow Properties Of Nanoparticle-based So...mentioning
confidence: 99%
“…Also, they inferred that NPs, by forming a velocity disturbance field, contributed to enhancement of the mass transfer phenomenon. As a result, this study became the basis of others’ studies in the field of mass transfer, and researchers made many efforts to increase CO 2 absorption by using various NPs. , For instance, Jung et al evaluated the effect of alumina NPs in methanol solution on CO 2 capture in an integrated gasification system combined with recycling. They revealed that the presence of alumina NPs in the methanol (as a base solvent) caused a higher CO 2 absorption of about 8.3% as compared to the base fluid .…”
Section: Introductionmentioning
confidence: 99%